2014
DOI: 10.3109/09638288.2014.911971
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes and coping after complete avulsion traumatic brachial plexus injury

Abstract: Patients encounter high levels of physical and psychological stress after complete avulsion BPI and must find ways to cope to adjust to their injuries. They face similar challenges to patients with spinal cord injuries, for whom many models describing coping and adjustment exist. Similar models could facilitate more complete adjustment and rehabilitation of BPI patients and help to reduce the prevalence of negative stress responses, including anger and depression. Future patients would benefit from a multidisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
(60 reference statements)
4
46
1
1
Order By: Relevance
“…Furthermore, others groups have used modified versions of the SWAP to evaluate patient populations who are subject to lifelong changes in appearance due to their disease and have reported meaningful results. 32 -up studies using this tool or the recently published body image scale are needed to confirm our findings and compare the magnitude of our findings to other IBD populations. 28 Second, few patients in our cohort had perianal disease or had undergone surgery by the end of follow-up.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, others groups have used modified versions of the SWAP to evaluate patient populations who are subject to lifelong changes in appearance due to their disease and have reported meaningful results. 32 -up studies using this tool or the recently published body image scale are needed to confirm our findings and compare the magnitude of our findings to other IBD populations. 28 Second, few patients in our cohort had perianal disease or had undergone surgery by the end of follow-up.…”
Section: Discussionsupporting
confidence: 53%
“…Our study confirms these effects and, by using qualitative techniques, provides new information about how patients begin to compensate for BPI. In another study, other investigators also used qualitative techniques to assess BPI by interviewing 12 patients at least 1 year postoperatively or post injury for nonsurgical patients [7]. This study reported patients had emotional effects including anger, frustration, depression, mourning, less energy, and decreased self-efficacy and selfesteem.…”
Section: Discussionmentioning
confidence: 99%
“…However, success of surgery currently is often measured by physicians according to physical examination and physician-derived scales that focus on motor function [2,5,12,13]. While these measures provide valuable information, they may miss aspects of the experience that are most important to patients, such as appearance and emotional well-being [2,7,16]. In addition, although there are valid patient-reported scales for disorders of the upper extremity, they may not capture the complex and severe physical and psychosocial impact of BPI [2,7,9,11,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobility and future consequences such as recurrent SCI-related health complications, inability to pursue education and career, and failure to participate in the community leads to a sequence of biopsychosocial and economic struggles throughout life (Biering-Sorensen et al, 2011;DeRoon-Cassini, de St Aubin, Valvano, Hastings, & Brasel, 2013;Franzblau & Chung, 2015). While in this state, individuals with SCI require healthcare and rehabilitation services to sustain their health and minimize risk for ill-health and death (Middleton et al, 2012;Oderud, 2014).…”
Section: Introductionmentioning
confidence: 99%